2019
DOI: 10.1186/s12245-019-0256-5
|View full text |Cite
|
Sign up to set email alerts
|

The influence of past experiences on future willingness to perform bystander cardiopulmonary resuscitation

Abstract: BackgroundThe influence of past familial experiences of receiving cardiopulmonary resuscitation (CPR) and medical help in various cardiac arrest and nonfatal cardiac events toward willingness to “pay it forward” by helping the next cardiac arrest victim was explored.MethodsUsing a validated questionnaire, 6248 participants were asked to rate their willingness to perform bystander chest compression with mouth-to-mouth ventilation and chest compression-only CPR. Their past familial experiences of receiving cardi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…concerns for woman 21% 291 resp. concerns for child 51% Cheng-Yu et al 2016 [ 50 ] Adults (≥20) 401 144 (unwilling to perform on stranger) 11% Compton et al 2003 [ 55 ] School teachers 201 180 64% of untrained 41% of trained Coons & Guy 2009 [ 56 ] Adults (≥18) 755 435 (who endorsed reasons) 19.4% stranger 26.4% (family) Cu 2009 [ 50 ] Caregivers of children presenting to the Emergency Department (≥18 years) 348 125 (unwilling to perform CPR on adult) 38% Dami 2010 [ 51 ] Call to Dispatch Centre with OHCA 738 73 medically appropriate who refused 3% Dobbie 2018 [ 53 ] Adults (≥16 years) 1027 1027 22% Donohoe 2006 [ 54 ] Adults (≥16 years) NR Focus groups (NR) NR (Qualitative theme identified) Dwyer 2008 [ 56 ] Adults (≥18) 1208 379 (not confident) 10% Han 2018 [ 58 ] Family members (≥18 years) of patients at risk of cardiac arrest 203 88 7% Huang 2016 [ 60 ] School and University students (13–21 years) 1407 546 (unwilling to perform on stranger) 68% …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…concerns for woman 21% 291 resp. concerns for child 51% Cheng-Yu et al 2016 [ 50 ] Adults (≥20) 401 144 (unwilling to perform on stranger) 11% Compton et al 2003 [ 55 ] School teachers 201 180 64% of untrained 41% of trained Coons & Guy 2009 [ 56 ] Adults (≥18) 755 435 (who endorsed reasons) 19.4% stranger 26.4% (family) Cu 2009 [ 50 ] Caregivers of children presenting to the Emergency Department (≥18 years) 348 125 (unwilling to perform CPR on adult) 38% Dami 2010 [ 51 ] Call to Dispatch Centre with OHCA 738 73 medically appropriate who refused 3% Dobbie 2018 [ 53 ] Adults (≥16 years) 1027 1027 22% Donohoe 2006 [ 54 ] Adults (≥16 years) NR Focus groups (NR) NR (Qualitative theme identified) Dwyer 2008 [ 56 ] Adults (≥18) 1208 379 (not confident) 10% Han 2018 [ 58 ] Family members (≥18 years) of patients at risk of cardiac arrest 203 88 7% Huang 2016 [ 60 ] School and University students (13–21 years) 1407 546 (unwilling to perform on stranger) 68% …”
Section: Resultsmentioning
confidence: 99%
“…concerns for woman 14% 291 resp. concerns for child 23% Chen et al 2017 [ 48 ] Adult laypersons (≥18 yrs) + 3 < 18 years 1841 1841 44% Cheng-Yu et al 2016 [ 50 ] Adults (≥20) 401 144 (unwilling to perform on stranger) 6% Cho et al 2010 [ 54 ] Lay people aged 11 years and over 890 539 (unwilling to perform CPR) 50% Cu 2009 [ 50 ] Caregivers of children presenting to the Emergency Department (≥18 years) 348 125 (unwilling to perform CPR on adult) 77% Dobbie 2018 [ 53 ] Adults (≥16 years) 1027 1027 19% Huang 2016 [ 60 ] School and University students (13–21 years) 1407 546 (unwilling to perform on stranger) 53% Iserbyt 2016 [ 63 ] Secondary school pupils 313 313 31% (girls) 23% (boys) Johnston 2003 [ 65 ] Adults (≥18 years) 4490 4490 2% Karuthan et al 2019 [ 78 ] College students 393 393 36% (HO stranger) 27% (HO family-member) Kanstad, Nilsen & Fredriksen 2011 [ 77 ] Secondary school students (16–19 years) 376 376 79% Maes et al 201...…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The main reasons for not performing CPR were panic, the perception of bystanders that they are not able to perform CPR correctly, and a fear of hurting the patient [ 38 ]. Familial experiences of receiving CPR were associated with an increase in responders’ willingness to perform CPR [ 39 ]. The UnityPhilly study, which established a network of volunteers to provide naloxone to those experiencing an opioid overdose, reported that 17% of the alerted volunteers accepted the alert, and 11.9% of the alerted volunteers arrived at the scene [ 34 ].…”
Section: Introductionmentioning
confidence: 99%